Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery

Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.